Salivary thromboplastic activity in diabetics and healthy controls. - (:unkn) unknown (My University, 2004)
Coagulative function of saliva derives from the thromboplastin found in saliva. It may establish hemostasis in the mouth. Salivary disfunction and changes in salivary composition and are frequent complications of diabetes. This study investigated the influence of some local etiologic and systemic factors on salivary thromboplastic activity (STA) in diabetics. In this study, cytological smears and biochemical tests were used. STA was measured by Quick's one stage method, serum glucose by the glucose oxidase method, and salivary protein by the method of Lowry. STA was almost the same in the diabetic and control groups. The only statistically significant difference within the diabetic group was found to be due to antibiotic usage. STA, i.e. clotting time, was 30% longer (114 s) ( p<0.05) and salivary protein (4.07 mg ml(-1)) ( p<0.1) was lower in diabetics not taking antibiotics than in those taking them. No such differences were observed in the healthy controls. Significant linear correlations ( p<0.05) with respect to STA were with salivary protein in the control group (r=0.61) and in the diabetic group (r=0.51) and with antibiotic usage (r=0.29), with leukocyte cell count (r=0.27) in the diabetic group. It can be concluded that salivary cells, proteins and antibiotic usage are important for STA.